Toot and Puddle - Hobbie, Holly (Boston, Mass. : Little, Brown, 1997)
Toot and Puddle are best friends with very different interests, so when Toot spends the year travelling around the world, Puddle enjoys receiving his postcards.
Lexile
3 8 13 17 19 21 25 29 33 38
Keywords: Pigs -- Fiction; Travel -- Fiction; Friendship -- Fiction; Postcards -- Fiction